If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3u + -1(-10) = -2 Multiply -1 * -10 3u + 10 = -2 Reorder the terms: 10 + 3u = -2 Solving 10 + 3u = -2 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 3u = -2 + -10 Combine like terms: 10 + -10 = 0 0 + 3u = -2 + -10 3u = -2 + -10 Combine like terms: -2 + -10 = -12 3u = -12 Divide each side by '3'. u = -4 Simplifying u = -4
| -2x^2-8=5x | | 5d+7e+7d+7e= | | -3a-(-3)=-3 | | 3x^2+7x=10 | | 4x+3=x+16 | | (3+2i)(7-6i)= | | -3u-4=-19 | | 5-x/4=-1 | | 2u+(-8)=-24 | | 2u+(-8)=-4 | | x-8=(-14) | | 0.6(a-3)=-0.3 | | 2v-7=11 | | -2a-(-4)=10 | | -3x=2(3x+8) | | 2v-10=-2 | | x/2=-13 | | -3z+(-8)=1 | | X/6-8=-1 | | 7y=2.1 | | -5R+85=13R | | 6Y+39+14Y=-1 | | 7y=10 | | 6Y+39+14Y= | | 3a-(4)=7 | | -x+53=5x+5 | | 3c-9=-15 | | 121-2x=43x+16 | | 6m-17ifm=3 | | 14x=-48 | | 4(3x-2)+9x=51 | | 1/2(x-3)=5 |